Interaction between metabolic syndrome and alcohol consumption, risk factors of liver fibrosis: A population‐based study. (11th March 2021) - Pose, Elisa; Pera, Guillem; Torán, Pere; Gratacós‐Ginès, Jordi; Avitabile, Emma; Expósito, Carmen; Díaz, Alba; Graupera, Isabel; Rubio, Ana B.; Ginès, Pere; Fabrellas, Núria; Caballeria, Llorenç
Abstract: Background and aims: Alcohol and metabolic syndrome (MS) coexist frequently as cofactors of liver disease. Previous studies suggest a deleterious effect of MS in advanced alcohol‐related liver disease (ArLD). However, it is unknow whether MS can increase the risk of liver fibrosis in early stages of ArLD. The aim of this study was to investigate the effect of MS on liver fibrosis in subjects with alcohol consumption from a population‐based cohort. Methods: The number of subjects include 1760(58%) of 3014 who were randomly selected from the community consumed alcohol and were classified as current drinkers, divided in moderate (n = 1222) or high‐risk drinkers (n = 275) (>21 units/week men, >14 units/week women for high‐risk drinkers), or former drinkers (n = 263). Liver fibrosis was estimated by measuring liver stiffness(LS) with transient elastography (TE). Results: Prevalence of significant LS using cutoff values of TE of 8 and 9.1kPa was increased in high‐risk compared with moderate or former drinkers and lifetime abstainers. In subjects with alcohol consumption, LS was associated with male gender, AST, ALT, years of consumption, and MS. In high‐risk drinkers, MS and intensity of consumption were the only factors associated with significant LS (OR 3.7 and 4.6 for LS ≥ 8 kPa and 3.9 and 9.2 kPa for LS ≥ 9.1 kPa, respectively). Presence of significant liver fibrosis in the liver biopsy was higher among high‐risk as compared with moderate or former drinkers. Conclusion: MS increases the risk of liver fibrosis in subjects with alcohol consumption. Among high‐risk drinkers, only MS and consumption of high amount of alcohol are associated with risk of liver fibrosis.